Social marketing approaches in Turkish illumination sector - Tunalı, Esra (My University, 1999)
Bu çalışmanın ana amacı, ampul firmalarının sosyal pazarlama açısından enerji tasarruflu ampullerle ilgili pazara yaklaşımlarını anlamaktır. Enerji krizi, gelişen dünyanın en önemli sorunlarından biridir. Teknolojinin gelişmesi ile birlikte insanoğlu daha rahat bir yaşam sürmektedir. Bu rahat yaşamın devam edebilmesi için çeşitli enerjiler kullanılmaktadır. Bunların arasında elektrik enerjisi en önemlisidir. Elektrik enerjisi insanların günlük hayatta en çok kullandığı ısınma, aydınlatma ve haberleşme için kullanılır. Ne yazık ki, elektrik enerjisi üreten santraller çevreyi kirletmektedirler. Dolayısı ile mevcut enerji kaynaklarında tasarruf yapmak uzun vadede enerji krizine çözüm getireceği gibi, çevreyi de koruyacaktır. Ayrıca, enerjiden tasarruf etmek talebi karşılamak için yeni santraller üretmekten daha ucuz ve kolay bir yoldur. Hükümetler, enerji tasarrufu için politikalar geliştirmekte ve toplumun refahı için toplumsal pazarlama teknikleri kullanarak insanları enerjiyi bilinçli kullanmaları için ikna ederler. Elektriğin yaklaşık %20-25 i aydınlatma tarafından tüketildiğinden aydınlatma sektörü enerji tasarrufu açısından önemli bir sektördür. Aydınlatma sektöründe faaliyet gösteren firmalar dünyanın enerji krizini azaltmaya katkıda bulunmak için sosyal pazarlama teknikleri uygulamalıdırlar. Türkiye'nin ciddi bir enerji sorunuyla karşılaştığını ve elektrik enerjisinin yaklaşık % 20 sinin aydınlatmada tüketildiğini düşünürsek, aydınlatma sektörü elektrik enerjisinin verimli kullanılması açısından önem kazanmaktadır. Bu çalışmada, elektrik enerjisi ampuller tarafından tüketildiği için sadece ampul firmaları incelenecektir. Tüketiciler de uzun vadeli refah için enerji tasarrufuna katkıda bulunmalıdırlar. Bu çalışmada, enerji tasarruflu ampullerle ilgili tüketicinin bilgisi ve yaklaşımları incelenecektir.

The main purpose of this study is to understand approaches of lamp firms in the market about energy saving lamps in terms of social marketing. Energy crisis is one of the important problem of developing world. By developing technologies, human being's life are become more comfortable. Various types of energies are used to continue this comfort. Electrical energy is the most important one out of energy types. In daily lives of people, electrical energy is used for heating, lighting and communication. Unfortunately, the environment is polluted by power plants which produce electrical energy. So, conservation of existing energy sources brings solutions for energy crisis in long term and protects the environment. Also, saving energy is the cheapest and easiest way relative to producing new power plants to supply demand. The governments develop policies to save energy and by applying societal marketing techniques, they convince people to use energy consciously for well-being of society. The illumination sector is an important sector from the point of view of energy saving because between 20-25% of electricity is consumed by lighting. The firms operating in illumination sector have important roles in appliying social marketing approaches to contribute to decreasing energy crisis of the world. Considering that Turkey has faced a serious energy problem and approximately 20% of electricity is consumed by lighting, the illumination sector gains importance from the point of view using electrical energy effectively. In this study, because electrical energy is consumed by lamps only lamp firms will be analyzed. Also, consumers should contribute to energy saving for long term welfare. In this study, the consumers' knowledge and attitudes towards the energy saving lamps will be analyzed. The field study shows that the Turkish government has no studies related with illumination sector in terms of energy saving. Also, there is no social marketing approaches is applied by lamp firms to spread the usage of the energy saving lamps. So, the research results are negative from the perspective of the government and the lamp firms. The only positive result of this study is if consumers is informed, they tend to buy energy saving lamps.
Keywords: Genel yönetim; Pazarlama yönetimi; Pazarlama_Yönetim